PENGARUH AI-PERSONALIZED RECOMMENDATION TERHADAP PURCHASE DECISION MELALUI PERCEIVED VALUE DENGAN MODERASI TRUST - Ni Nyoman Sri Utari Krisnanda; I Kadek Yoga Rama Parmita (Jurnal Pijar, 2026)
This study aims to analyze the effect of AI-Personalized Recommendation on Purchase Decision among TikTok Shop users with Perceived Value as a mediating variable and Trust as a moderating variable. The research employed a quantitative approach with a survey design. The population consisted of TikTok Shop users residing in Bali Province, with a sample of 150 respondents selected using purposive sampling technique. Data were collected through an online questionnaire measured using a Likert scale. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that AI-Personalized Recommendation has a positive and significant effect on Perceived Value and Purchase Decision. Perceived Value was found to significantly influence Purchase Decision and act as a mediating variable. Trust also has a significant direct effect on Purchase Decision, but it does not moderate the relationship between Perceived Value and Purchase Decision. The findings imply that optimizing AI-based recommendation systems and enhancing consumer perceived value are essential strategies to improve purchase decisions in social commerce platforms